Approaching Collectivity Collectively: A Multi-Disciplinary Account of Collective Action - Thonhauser, Gerhard; Weichold, Martin (Frontiers in Psychology, 2021)
There has been considerable progress in investigating collective actions in the last decades. However, the real progress is different from what many scholars take it to be. It lies in the fact that there is by now a wealth of different approaches from a variety of fields. Each approach has carved out fruitful mechanisms for explaining collective action, but is also faced with limitations. Given that situation, we submit that the next step in investigating collective action is to acknowledge the plurality of approaches and bring them into dialogue. With this aim in mind, the present article discusses the strengths and weaknesses of some of the to our mind most relevant approaches to collective action in current debates. We begin with the collective intentionality framework, the team reasoning approach, and social identity theory. Then, we move to ecological social psychology, participatory sense-making, and, through the lenses of those frameworks, dynamical systems theory. Finally, we discuss practice theory. Against this background, we provide a proposal for a synthesis of the successful explanatory mechanisms as they have been carved out by the different research programs. The suggestion is, roughly, to understand collective action as dynamical interaction of a self-organizing system with its environment, shaped by a process of collective sense-making.